To cross or not to cross the cervicothoracic junction in multilevel posterior cervical fusion: a systematic review and meta-analysis - Chang, Min Cheol; Kim, Gang-Un; Choo, Yoo Jin; Lee, Gun Woo (The spine journal, 2022)
Inclusion of the cervicothoracic junction (CTJ) during decision-making regarding the surgical level of multilevel posterior cervical fusion (PCF) surgery remains the subject of debate, largely due to a lack of studies on the topic. Thus, we considered that meta-analysis based on recent high-quality clinical studies might enable better-informed decision-making regarding the selection of the distal level of multilevel PCF, particularly concerning the advisability of crossing the CTJ. To compare the outcomes of patients who underwent multilevel PCF with or without crossing the CTJ (the thoracic and cervical groups, respectively) by the distal construct. A systematic review and meta-analysis. We searched the Cochrane, Embase, and Medline databases for articles that compared the intra- and post-operative outcomes of patients who underwent multilevel PCF surgery with or without extension of surgery to include the CTJ, using January 7, 2021, as the publication cutoff date. Group differences in primary and secondary outcome measures were analyzed for significance (p<.05). All reported means were pooled. A total of 1,904 publications were assessed, and eight studies met the study criteria. The cervical group had a significantly greater fusion rate than the thoracic group (p=.03), but higher adjacent segment disease (ASD) and reoperation rates (ASD: OR=3.15, p=.007; reoperation: OR=1.93, p=.008). As regards surgical outcomes, mean blood loss was less and operation time was shorter in the cervical group (p=.008 and .009, respectively). However, mean hospital stays were not significantly different (p=.12), and neither were the rates of complications, such as metal failure and hematoma. In the current study, fusion rate, blood loss, and operation time were better in the cervical group than in the thoracic group, but ASD incidence and ASD-related complication rates at the CTJ were greater in the cervical group. For patients with higher risk factors for adjacent-segment degeneration, crossing the CTJ may be warranted.